Quantum property of solid hydrogen as revealed by high-resolution laser spectroscopy: Spectroscopy in Cryocrystals and Matrices - Katsuki, Hiroyuki; Fushitani, Mizuho; Momose, Takamasa (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Pure vibrational overtone transitions of solid parahydrogen were studied using high-resolution laser spectroscopy. Extremely narrow spectral linewidth (~20 MHz) allowed us to observe richspectral structure that originates in subtle intermolecular interactions in the crystal. It was found that anisotropy of the distribution of zero-point lattice vibration of hydrogen molecules perturbsthe energy levels of the vibrationally excited states significantly. Large amplitude of the zero-point lattice vibration being an intrinsic nature of quantum solids, was directly observed from the present high-resolution spectroscopy. The first observation of a pure vibrational overtone transitionof solid orthodeuterium is also discussed.